Proceeding report of the Symposium on Hidradenitis Suppurativa Advances (SHSA). Issue 1 (15th November 2017) - Mehdizadeh, Ali; Alavi, Afsaneh; Alhusayen, Raed; Bauer, Boris; Bechara, Falk G.; Bourcier, Marc; Brassard, Alain; Djamei, Vahid; Dutz, Jan; George, Ralph; Ghias, Mondana; Gooderham, Melinda; et al.
Abstract : Abstract: Hidradenitis Suppurativa (HS) is a chronic debilitating skin condition that impairs the productivity and the quality of patients` lives. HS has recently drawn lots of attention among scholars to further expand their knowledge but it still loads with uncertainties and gaps to be explored. This publication addresses these uncertainties, and provides a road‐map for researchers, scholars and clinicians from different disciplines for their future studies about HS. This is a proceeding report of the first Symposium on Hidradenitis Suppurativa Advances (SHSA), and it reviews the scientific sessions about the epidemiology, pathophysiology, presentations, and management of HS. This symposium was a great opportunity for experts in the HS field to exchange their knowledge, and improve their mutual understanding of this disease.